Morphological Analysis of River Characteristics in Musi Rawas Utara Regency - Stephanie, Kiki Nidya; Setiadi, Rukuh (Jurnal Pembangunan Wilayah dan Kota, 2024)
Effective watershed management requires the efficient collection, storage, and use of runoff water, as well as the recharge of groundwater. This study will employ morphometric analysis to determine the characteristics of the rivers flowing through one of the districts of the Province of South Sumatera, Musi Rawas Utara (Muratara). Using DEM data and GIS software, this study conducted a quantitative-descriptive analysis to obtain quantitative information about the watershed. The acquired numbers are interpreted descriptively to provide a description of the watershed's characteristics and their implications for rivers in Muratara. The eighth-order rivers of Muratara Regency are classified as major rivers. A mean bifurcation ratio (Rb) of 3.98 indicates that geological features have no effect on the typical flat drainage pattern. On average, the drainage density of the watersheds was moderate, but a few locations had a very high drainage density range, indicating their erodibility. The basins of rivers with low circularity and elongation ratios (0.19 and 0.48, respectively) are elongated and have a steep slope. The morphometric research reveals that the Muratara rivers have abundant water resources and are also predicted to experience numerous water-related disasters. Using morphometric knowledge, however, the local government could develop mitigation and planning systems for river management. Future measures must include ensuring that adequate drainage systems are in place and that all construction adheres to the principles of proper land management.